Non-charismatic waterbodies and ecosystem disservices: Mine pit lakes are underrepresented in the literature - Bernasconi, Rachele; Lund, Mark A.; Blanchette, Melanie L. (Frontiers in Microbiology, 2022)
Pit lakes are one of the greatest legacies of open-cut mining. Despite the potential hazards of these lakes, they represent newly formed ecosystems with great scientific and ecological potential. Although thousands of pit lakes occur on every inhabited continent, with more being created, the microbial ecology of pit lakes is relatively under-researched. We evaluated the current state of microbial research in pit lakes by performing a Web of Science search and creating a literature database. Study lakes were categorized according to location and water quality (pH and conductivity) which is a key community and environmental concern. Research technology employed in the study was also categorized. We compared research effort in lakes, rivers, and streams which are the more “charismatic” inland aquatic ecosystems. Pit lake publications on microbes from 1987 to 2022 (n = 128) were underrepresented in the literature relative to rivers and streams (n = 321) and natural lakes (n = 948). Of the 128 pit lake publications, 28 were within the field of geochemistry using indirect measures of microbial activity. Most pit lake microbial research was conducted in a few acidic lakes in Germany due to social pressure for remediation and government initiative. Relatively few studies have capitalized on emerging technology. Pit lake microbial research likely lags other more charismatic ecosystems given that they are viewed as performing “ecosystem disservices,” but this is socially complex and requires further research. Improving understanding of microbial dynamics in pit lakes will allow scientists to deliver safer pit lakes to communities.